Structural, atomic and electrostatic force microscopy analyses on YBCO/PBCO/LCMO superlattices - Bonilha, Marcel Miyamura [UNESP]; Dos Santos, Dayse Iara [UNESP]; Mohallem, Nelcy Della Santina; Seara, Luciana Moreira; Yonamine, Anne Hitomi [UNESP] (FapUNIFESP (SciELO), 2017)
In order to study the influence of the insulator layer thickness in heterojunctions, (YBa2Cu3O7-d[20nm]/ PrBa2Cu3Oy/La1/3Ca2/3MnO3[20nm])x20 superlattices were prepared by pulsed laser deposition using three PrBa2Cu3Oy layer thicknesses and two different sequences of deposition. Sample characterization showed primitive orthorhombic crystalline arrangement for YBCO and LCMO, however, a slightly disordered crystalline structure was observed for the sample having thicker PBCO layer. Microscopy analyses indicated influence of both parameters (PBCO thickness and sequence of deposition) on the texture of the upper layer. Electrostatic Force Microscopy analyses showed evident contrast on the phase images, what suggests that samples are conductive. Distinct surface aspect and highest contrast (highest shift in the electric mode phase image) were observed for the surface of the sample in which the sequence of deposition was inverted, with the YBCO ceramic as upper layer of the superlattice.
Keywords: AFM and EFM; Structural analysis; Superconductors; Superlattices